Influence of artificial seawater on the VHCF behavior of different steels. Issue 2 (20th October 2022) - Wickmann, Carsten; Sander, Manuela
Abstract: The fatigue properties of a high‐strength steel, a structural steel, and a duplex stainless steel in artificial seawater were investigated. Consequently, a test chamber for the existing ultrasonic test stand was implemented. The experiments were performed with smooth specimens at a loading with R  = −1 up to 2 · 10 9  cycles. The specimens were fully submerged in artificial seawater. The fatigue data were statistically evaluated using the pearl string method and compared to different SN curves from the literature in air. The results show continuously decreasing SN curves under seawater conditions for all materials, with no detectable fatigue limit. Fracture surface investigations reveal large corrosion areas for the structural steel with, generally, no clear crack initiation location. The duplex stainless steel shows less corrosion pits but a high degree of scatter of the SN data. For the high‐strength steel, multiple crack initiation locations were observed from the surface. Highlights: A seawater test rig extension was introduced to perform fully submerged VHCF experiments Fatigue tests were performed on three different steels at R  = −1 up to 2 · 10 9  cycles The statistically evaluated SN curves show a high scatter and no fatigue limit Fracture surface investigations reveal different crack initiation from specimen surfaces